INTEGRATION OF ISLAMIC BOARDING SCHOOL VALUES IN CONTINGENCY COMMUNICATION STRATEGIES FOR EFFECTIVE CRISIS MANAGEMENT - Sabiq Al Hadi , Moh; Aimah , Siti (As-Sulthan Journal of Education, 2024)
This study aims to identify and integrate pesantren values into contingency communication strategies to create more effective crisis management. The focus of the study is on the application of values such as honesty, exemplary behavior, deliberation, and sense of responsibility in crisis management in pesantren. The approach used is qualitative with a case study type, where data is collected through in-depth interviews with pesantren managers, kiai, senior santri, and communication practitioners involved in crisis management, as well as participatory observation in crisis situations. The results of the study indicate that honesty as the main value of pesantren can accelerate crisis recovery by maintaining transparency and credibility of information. The exemplary behavior of pesantren leaders has proven effective in providing a sense of calm and clear direction to the community and santri. In addition, the application of the principle of deliberation in decision-making during a crisis allows for the achievement of more inclusive solutions that are accepted by various parties. By integrating these pesantren values, a pesantren-based crisis communication model can be produced, which is not only more humane, but also effective in creating communication that builds trust and reduces fear in the midst of a crisis.